Designing Immersive Virtual Environments for Human Behavior Research - Neo, Jun Rong Jeffrey; Won, Andrea Stevenson; Shepley, Mardelle McCuskey (Frontiers in Virtual Reality, 2021)
What are strategies for the design of IVEs to understand environments’ influence on behaviors? To answer this question, we conducted a systematic review to assess peer-reviewed publications, and conference proceedings on experimental and proof-of-concept studies that described the design, manipulation, and setup of the IVEs to examine behaviors influenced by the environment. Eighteen articles met the inclusion criteria. Our review identified key categories and propose strategies in the following areas for consideration when deciding on the level of detail that should be included when prototyping IVEs for human behavior research. (1) the appropriate level of detail (primarily visual) in the environment: important commonly found environmental accessories, realistic textures, computational costs associated with increased details, and minimizing unnecessary details. (2) Context: contextual element, cues, and animation social interactions, (3) Social cues: include computer-controlled agent-avatars when necessary and animating social interactions. (4) self-avatars, navigation concerns, and changes in participants’ head directions. (5) Non-visual sensory information: haptic feedback, audio, and olfactory cues.